2013
DOI: 10.1227/neu.0b013e318282a558
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Outcomes of Static vs Expandable Titanium Cages After Corpectomy

Abstract: Expandable cages had higher rates and risk of subsidence in comparison with static cages. When subsidence was present, expandable cages had greater magnitudes of subsidence. Other factors including footplate-to-vertebral body endplate ratio, prongs, extent of supplemental posterior fusion, spinal region, and diagnosis also impacted subsidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 29 publications
1
55
1
5
Order By: Relevance
“…Contrarily, Lau et al [25] compared subsidence rates between static and expandable cages throughout the spine in a retrospective cohort analysis and found that expandable cages had an increased odds ratio of subsidence at 1 and 12 months, and there was an increased risk of subsidence at 1 month with osteomyelitis, footplate-to-body ratio <0.5, no posterior fusion or fusion <2 levels above and below the corpectomy. The use of prongs on the cage end plate decreased the risk of subsidence.…”
Section: Subsidencementioning
confidence: 99%
“…Contrarily, Lau et al [25] compared subsidence rates between static and expandable cages throughout the spine in a retrospective cohort analysis and found that expandable cages had an increased odds ratio of subsidence at 1 and 12 months, and there was an increased risk of subsidence at 1 month with osteomyelitis, footplate-to-body ratio <0.5, no posterior fusion or fusion <2 levels above and below the corpectomy. The use of prongs on the cage end plate decreased the risk of subsidence.…”
Section: Subsidencementioning
confidence: 99%
“…[1][2][3][4][5] A new advanced method is use of expandable titanium cages which allow easy replacement with in situ expansion and reproduction of the sagittal profile. [9][10][11][12][13] Stabilization can be achieved by additional anterior plating or posterior stabilization by a rod and screw system. Alternatively, a direct fixation of the cages with fixation wings is possible, a combination of two systems in one -cage and fixation system.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence to suggest that despite the greater surface contact area, expandable cages have a trend for higher subsidence rates when compared to fixed cages [31][32]. Some biomechanical assessments of expandable cages suggest associated higher subsidence rates and intraoperative fractures during deployment [30][31].…”
Section: Discussionmentioning
confidence: 99%